Age Dependent Dysfunction of Mitochondrial and ROS Metabolism Induced by Mitonuclear Mismatch - Pichaud, Nicolas; Bérubé, Roxanne; Côté, Geneviève; Belzile, Claude; Dufresne, France; Morrow, Geneviève; Tanguay, Robert M.; Rand, David M.; Blier, Pierre U. (Frontiers in Genetics, 2019)
Mitochondrial and nuclear genomes have to coevolve to ensure the proper functioning of the different mitochondrial complexes that are assembled from peptides encoded by both genomes. Mismatch between these genomes is believed to be strongly selected against due to the consequent impairments of mitochondrial functions and induction of oxidative stress. Here, we used a Drosophila model harboring an incompatibility between a mitochondrial tRNAtyr and its nuclear-encoded mitochondrial tyrosine synthetase to assess the cellular mechanisms affected by this incompatibility and to test the relative contribution of mitonuclear interactions and aging on the expression of impaired phenotypes. Our results show that the mitochondrial tRNA mutation caused a decrease in mitochondrial oxygen consumption in the incompatible nuclear background but no effect with the compatible nuclear background. Mitochondrial replication increased in the incompatible genotype but that increase failed to rescue mitochondrial functions. The flies harboring mismatch between nuclear and mitochondrial genomes had almost three times the relative mtDNA copy number and fifty percent higher rate of hydrogen peroxide production compared to other genome combinations at 25 days of age. We also found that aging exacerbated the mitochondrial dysfunctions. Our results reveal the tight interactions linking mitonuclear mismatch to mitochondrial dysfunction, mitochondrial DNA replication, ROS production and aging.